1998
DOI: 10.1016/s0960-9822(98)70297-0
|View full text |Cite
|
Sign up to set email alerts
|

Calcium triggers calcineurin-dependent synaptic vesicle recycling in mammalian nerve terminals

Abstract: Our results suggest that dynamin-dependent synaptic vesicle endocytosis is triggered by calcium influx occurring upon nerve-terminal depolarisation. An essential mediator of calcium's effect is calcineurin, the activation of which leads to dephosphorylation of at least four proteins implicated in endocytosis-dynamin, amphiphysin 1, amphiphysin 2 and synaptojanin. Our findings also imply that endocytosis and exocytosis may occur in tandem in vivo simply because they share a responsiveness to calcium influx, rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
224
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(234 citation statements)
references
References 46 publications
9
224
1
Order By: Relevance
“…Dephosphorylation of dynamin 1 by calcineurin decreases its GTPase activity (Liu et al, 1994) and enhances interaction with its partners . The immunosuppressants CsA and Tacrolimus (FK506) are calcineurin inhibitors reported to inhibit synaptic vesicle recycling, a dynamin 1-controlled event (Marks and McMahon, 1998) and to interfere with podosome organization (Ochoa et al, 2000). We found CsA to dramatically decrease both the number of degrading cells and the total area of degradation.…”
Section: Baldassarre Et Almentioning
confidence: 81%
“…Dephosphorylation of dynamin 1 by calcineurin decreases its GTPase activity (Liu et al, 1994) and enhances interaction with its partners . The immunosuppressants CsA and Tacrolimus (FK506) are calcineurin inhibitors reported to inhibit synaptic vesicle recycling, a dynamin 1-controlled event (Marks and McMahon, 1998) and to interfere with podosome organization (Ochoa et al, 2000). We found CsA to dramatically decrease both the number of degrading cells and the total area of degradation.…”
Section: Baldassarre Et Almentioning
confidence: 81%
“…To test whether clathrin-dependent endocytosis of NMDA receptors (Vissel et al, 2001;Nong et al, 2003) is also involved in the 5-HT 1A modulation of NMDAR currents, we dialyzed neurons with a dynamin inhibitory peptide that interferes with the binding of amphiphysin with dynamin and therefore prevents endocytosis through clathrin-coated pits (Grabs et al, 1997;Marks and McMahon, 1998). We found that the effect of 8-OH-DPAT was intact in neurons loaded with the dynamin inhibitory peptide (50 M; 21.5 Ϯ 2.1%; n ϭ 4) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Internalization is accompanied by dephosphorylation of GluR1 at a PKA phosphorylation site 13 ; however, dephosphorylation of a component of the endocytotic machinery might alternatively be required. Indeed, calcineurin is known to dephosphorylate several proteins involved in endocytosis, including dynamin 24,25 .…”
Section: Activity Drives Removal Of Amparsmentioning
confidence: 99%